IMPROVING STUDENTS’ READING COMPREHENSION ACHIEVEMENT THROUGH THE CONCEPT ATTAINMENT MODEL - Harahap, Nova Jayanti (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
This study aims at improving students’ achievement in reading comprehension applying The Concept Attainment Model by conducting classroom action research. The subjects of this research the first semester students Majoring in Economics from Yayasan Universitas Labuhan Batu Rantauprapat. The number of the students was 20 students. There were two kinds of data collected during the study, quantitative and qualitative data. The instrument for collecting the quantitative data was objective test of reading comprehension, while the instruments for qualitative data were gathered through observation sheet, diary notes and check list. Based on the data analysis, the mean of the students score in pre-test 51, in cycle I was 61.75, and in cycle II was 80.50. The conclusion is that The Students Concept Attainment Model can improve the students’ achievement in reading comprehension.